La economía social y solidaria como vía para el buen vivir The social and solidarity economy as a way to buen vivir - Unai VILLALBA-EGUILUZ; Juan Carlos PÉREZ-DE-MENDIGUREN (Revista Iberoamericana de Estudios de Desarrollo)
The Social and Solidarity Economy (SSE) encompasses a wide range of economic endeavors and logics with the potential to deploy alternative «economies» —in varying degrees— to the capitalist system. The ESS is an indispensable reference to move from conventional development models to the paradigm of buen vivir. In this article, it is showed which are the principles of the SSE and to what extent they converge with the dimensions and Good Living Objectives and with the strategies to achieve it. We emphasize the need to implement strategies oriented to the regulation, redistribution, resizing and decommodification of the economic sphere. These four orientations should be driven by public policies, but, at the same time, the SSE organizations themselves are already implementing them from practice thanks to their principles and values. We propose ways of promoting SSE such as responsible public procurement, social markets and local economic circuits, recovery of sovereignty (food, energy, ethical finance and social currencies), reconceptualization of work and well-being for the sustainability of life.